2014
DOI: 10.1177/0269215514537093
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance training before and after total hip and knee arthroplasty: a systematic review

Abstract: PRT is safe and feasible before and/or after THA. PRT is safe, but the methodological quality of existing evidence permits no conclusion on the effectiveness of PRT before and/or after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 63 publications
(93 reference statements)
1
62
2
5
Order By: Relevance
“…Adjusted betweengroup differences are x(95%CI). Between-group difference at follow-up is adjusted for baseline, sex, age and BMI the content of progressive RT 15,11 . Eight weeks of slow velocity progressive RT (applied both before and after surgery) was reported to increase leg muscle strength in hip OA patients).…”
Section: Efficacy Of Preoperative Exercise Therapy In Hip Oa Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusted betweengroup differences are x(95%CI). Between-group difference at follow-up is adjusted for baseline, sex, age and BMI the content of progressive RT 15,11 . Eight weeks of slow velocity progressive RT (applied both before and after surgery) was reported to increase leg muscle strength in hip OA patients).…”
Section: Efficacy Of Preoperative Exercise Therapy In Hip Oa Patientsmentioning
confidence: 99%
“…Concerns has been raised according to the content of the exercise programs and their therapeutic validity, in particular according to the intensity and progression of training 11,13 . These considerations are supported by a resent systematic review of progressive resistance training (RT) in relation to joint replacement surgery that was only able to identify a single RCT containing progressive RT 14,15 . The study indicated that progressive RT of low velocity did improve post-operative physical functioning, however since the intervention group received the intervention both before and after surgery it was not possible to determine the isolated effect of the preoperative intervention 14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, low pre-operative function is a significant risk factor for increased LOS and predictive of worse longer-term function (Biring et al, 2007;Davis et al, 2006;Yeung et al, 2010). There are no studies of rehabilitation before RTHR but there is some evidence that exercise can improve pain, muscle strength and function before primary THR (Gill & McBurney, 2013;Skoffer, Dalgas, & Mechlenburg, 2015;Wang et al, 2016) although the size and clinical importance of these changes is debated. Whether pre-operative rehabilitation focused on optimizing function before RTHR is safe, feasible and can improve outcomes seems relevant to investigate.…”
Section: Pre-operative Carementioning
confidence: 99%
“…Reductions in strength can persist and affect function late after surgery (Okoro, Lemmey, Maddison, & Andrew, 2012 There are no studies of rehabilitation after RTHR, but trials following primary THR provide little support for the use of NWB exercises without sufficient resistance and progression (although there is also no high-level evidence that they are ineffective) (Di Monaco & Castiglioni, 2013). In contrast, there is increasing evidence in primary THR populations that using PRT to individually set then progress both exercise intensity and training volume to achieve overload is well-tolerated and can benefit strength and function (Di Monaco & Castiglioni, 2013;Okoro et al, 2012;Skoffer et al, 2015).…”
Section: Inpatient Rehabilitationmentioning
confidence: 99%
“…We have previously published a systematic review on progressive resistance training before and after total knee arthroplasty (2). We found that the methodologic quality of existing evidence did not permit us to reach a conclusion on the effectiveness of progressive resistance training before and/or after total knee arthroplasty, and we are therefore encouraged that studies on this topic are now emerging (1,3).…”
mentioning
confidence: 99%